2020
DOI: 10.1302/2633-1462.18.bjo-2020-0112.r1
|View full text |Cite
|
Sign up to set email alerts
|

Waiting lists for symptomatic joint arthritis are not benign

Abstract: Aim Restarting elective services presents a challenge to restore and improve many of the planned patient care pathways which have been suspended during the response to the COVID-19 pandemic. A significant backlog of planned elective work has built up representing a considerable volume of patient need. We aimed to investigate the health status, quality of life, and the impact of delay for patients whose referrals and treatment for symptomatic joint arthritis had been delayed as a result of the response to COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…End-stage symptomatic arthritis is not a benign condition. 13 Patients can suffer mentally, physically, and may struggle to return to work. 14 Under normal circumstances, 12% to 19% of patients awaiting THA and TKA, are defined as living in a health state “worse than death” according to the EuroQol five-level dimension (EQ-5D).…”
Section: Discussionmentioning
confidence: 99%
“…End-stage symptomatic arthritis is not a benign condition. 13 Patients can suffer mentally, physically, and may struggle to return to work. 14 Under normal circumstances, 12% to 19% of patients awaiting THA and TKA, are defined as living in a health state “worse than death” according to the EuroQol five-level dimension (EQ-5D).…”
Section: Discussionmentioning
confidence: 99%
“… 28 The authors suggested that all non-critical surgery should be postponed. However, to the patient, delay of planned surgery may result in significant harm to physical and mental health, 2 , 3 irreversible disability, loss of income, and in some conditions such as cancer, reduced life expectancy. 29 , 30 To society, delay is likely to result in missed education, unemployment, and an increased demand on the healthcare system and welfare state.…”
Section: Discussionmentioning
confidence: 99%
“… 2 On the other hand, some patients may prefer to defer planned surgery due to fear of contracting the disease during hospitalization, which may result in loss of function and reduced life expectancy as a result of delay. Waiting is far from benign—patients are in physical and psychological distress, 3 - 5 and may get worse 6 and consequently benefit less from surgery. 7 Furthermore, cancellation due to COVID-19 has compounded existing symptoms with significant anxiety, related to job insecurity and economic uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Inpatient stay is associated with risk and there is an argument for focusing on day case work or healthy American Society of Anesthesiologists (ASA) grade 17 1 patient mix, 2 but this may be to the detriment of older, less healthy individuals and does not account for the socioeconomic impact of providing continued nonoperative care for long-term treatable surgical conditions, which can lead to worsening comorbidity. 18 , 19 …”
Section: Discussionmentioning
confidence: 99%